Applying the SMART methodology within decision support systems to evaluate the suitability of oil palm fruit for production - Roy, Antonio; Serli (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
Palm oil holds a significant position within Indonesia's commodities sector due to the high economic value per hectare that oil palm plantations yield, making it one of the country's vital commodities. Evaluating the quality of oil palm fruits fit for production requires a precise mechanism. One effective approach is the application of the SMART method, which stands for Simple Multi-Attribute Technique. SMART is a model employed to identify the optimal alternative from a set of options based on specific criteria.The outcomes of this study indicate several key findings. Firstly, the decision support system developed accelerates data processing during the decision-making process to determine the suitability of oil palm fruit for production. Additionally, the application of this decision support system adapts to the dynamic nature of weight value determination, making it adjustable to varying needs in assessing the quality of oil palm fruit production. The SMART method proves to be highly suitable for decision-making, especially for rapidly and accurately determining the production-worthy quality of oil palm fruit. Notably, the test results using the SMART method yielded a remarkable accuracy rate of 100%.